2018
DOI: 10.1063/1.5019805
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical approach for positron annihilation spectra of atoms and molecules beyond plane-wave approximation

Abstract: We report theoretical calculations of positron-electron annihilation spectra of noble gas atoms and small molecules using the nuclear orbital plus molecular orbital method. Instead of a nuclear wavefunction, the positronic wavefunction is obtained as the solution of the coupled Hartree-Fock or Kohn-Sham equation for a positron and the electrons. The molecular field is included in the positronic Fock operator, which allows an appropriate treatment of the positron-molecule repulsion. The present treatment succee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Other areas for future investigation are calculations of binding energies for nitriles, alcohols, aldehydes, ketones, formates, and acetates, for which many binding energies are known from the measurements [29]. Calculations can also be extended to the annihilation γ -ray spectra, for which the experimental data [77] have only recently started to be investigated [78,79]. We have previously shown that the model-correlation-potential method can be used to calculate low-energy elastic scattering and direct annihilation rates for small nonpolar molecules [43], and it may be possible to also use the method to compute direct annihilation rates for polar molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Other areas for future investigation are calculations of binding energies for nitriles, alcohols, aldehydes, ketones, formates, and acetates, for which many binding energies are known from the measurements [29]. Calculations can also be extended to the annihilation γ -ray spectra, for which the experimental data [77] have only recently started to be investigated [78,79]. We have previously shown that the model-correlation-potential method can be used to calculate low-energy elastic scattering and direct annihilation rates for small nonpolar molecules [43], and it may be possible to also use the method to compute direct annihilation rates for polar molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the annihilation rates, we will also use the bound-state positron wave functions to compute annihilation γ-ray spectra, where much of the experimental data 90 remained unexplained for a long time 91 and have only started to be explored now. 92…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used to make predictions for other molecular species, to guide future experimental effort and provide comparisons for more sophisticated quantum-chemistry calculations. The positron wave function can also be used to calculate the annihilation γ spectra, where much of the experimental data [41] still awaits theoretical analysis [50].…”
mentioning
confidence: 99%